Legal Protection of the Right to Health Service Guarantee for Hospital Patients - Meutia, Cut Yeni; Sidi, Redyanto; Maulana, Abdul Rahman (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: The right to health care is a human right guaranteed in Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia.Purposes of the Research: This study aims to analyze the implementation of legal protection of the right to health care security for patients at the Malahayati Medan Islamic Hospital (RSIM) based on Law Number 17 of 2023 concerning Health.Methods of the Research: The research method used is normative-empirical, by analyzing relevant laws and regulations as well as health service practices at RSIM through observation and interviews.Results Main Findings of the Research: The results showed that RSIM has implemented legal protection of patient rights through various mechanisms, such as providing clear medical information, implementing informed consent, access to medical records, and transparent complaint services. In addition, Islamic values are applied in every aspect of service, creating an atmosphere that supports patient comfort and satisfaction. However, implementation challenges are still faced, including patients' lack of understanding of rights and obligations, limited resources, and ineffective communication between medical personnel and patients. This study concludes that while RSIM has complied with the national regulatory framework in protecting patient rights, strategic steps are needed to improve patient education, strengthen resource capacity, develop information technology, and improve the effectiveness of medical communication. By addressing these challenges, RSIM is expected to become a model hospital that excels in the legal protection of patients' rights in Indonesia.